Preliminary investigations into a commercial thermal fingerprint developer for the visualisation of latent fingermarks on paper substrates - Fritz, Patrick; Van Bronswijk, Wilhelm; Fisher, D.; Lewis, Simon (International Association for Identification, 2014)
The Thermal Fingerprint Developer (TFD-2) developed by Foster and Freeman is the first commercially available instrument to solely utilise heat treatment to visualise latent fingermarks. The chemical-free TFD-2 was able to develop latent fingermarks on a variety of substrates. The manufacturer’s guidelines with regard to the optimal treatment settings were suitable for the more common substrates such as white copy paper; however, new protocols were required for the treatment of thermal paper. TFD-2’s ability to develop these samples and its use in sequence with traditional chemical reagents, such as 1,2-indanedione and physical developer, was demonstrated. The thermal developer may offer quick and easy heat application options for existing fingermark development reagents. It was found, however, that the TFD-2 developed samples lacked the detail and contrast afforded by conventional amino acid sensitive reagents under most conditions.